The Meaning of Fasting in Contextual Interpretation Interpretation of Ma'na cum Maghzah in Q.S. Al-Baqarah verse 183 - Akhmad Ja'far Shodiq; M. Mukhid Mashuri; Wiwin Ainis Rohti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Ma'na cum maghzāh approach initiated by Prof. Sahiron Syamsuddin. This research is based on the understanding that fasting is not just a ritual of holding back hunger and thirst, but rather a form of worship that contains deep spiritual, social, and moral dimensions. Through the ma'na cum maghzāh method, this article explores the literal meaning (ma'na) of the verse and explores the goals, wisdom, and moral messages (maghzāh) that are relevant to the challenges of contemporary life. The results of the study show that fasting, as mandated in the Qur'an, has the ultimate goal of achieving piety, which is not only vertical (relationship with Allah) but also horizontal (social relations). This approach interprets fasting as a means of tazkiyatun nafs (purification of the soul) and character formation that has implications for the creation of spiritual and social awareness, fostering empathy, justice, self-control, and social solidarity. This article concludes that a contextual understanding of fasting through the lens of ma'na cum maghzāh can present a more applicable and transformative meaning of worship for Muslims in facing the complexities of modern life.